Challenges To Professionalism Amongst Medical Students in Their Undergraduate Curriculum - Shrivastava, Saurabh; Shrivastava, Prateek; Joshi, Abhishek (National Journal of Community Medicine, 2023)
Practicing medicine is a stressful and complex process, wherein a lot is expected of the doctors and they have to be professional in their approach while discharging their duties. Acknowledging the importance of professionalism in medical practice, the practice of teaching and assessing professionalism has begun in most medical institutions. Even though a humble beginning has been made, in various settings it has been reported that medical students and/or doctors don’t behave professionally in their workplace. A wide range of challenges involving different stakeholders have been identified that play their part in hindering the medical students and practicing doctors to discharge their role as a professional. To conclude, professionalism is an important trait for all medical students to become successful in their clinical practice. However, the pathway to train medical students in professionalism is full of challenges. The need of the hour is to identify these challenges and devise solutions to overcome them to strengthen the overall process of training and assessment.